Folic Acid Attenuates High-Fat Diet-Induced Osteoporosis Through the AMPK Signaling Pathway - He, Haiting; Zhang, Yaxi; Sun, Yue; Zhang, Yanwei; Xu, Jingjing; Yang, Yuzhen; Chen, Jihua (Frontiers in Cell and Developmental Biology, 2022)
Objective: Obesity caused by a high-fat diet (HFD) will expand adipose tissue and cause chronic low-grade systemic inflammation, leading to osteoporosis. Folic acid is a water-soluble vitamin that plays an important role in regulating blood lipids and antioxidants. However, the effects and underlying mechanisms of folic acid in osteoporosis induced by a high-fat diet remain poorly understood. This study aimed to investigate the effect of folic acid on the bone health by using high-fat diet (HFD)-induced osteoporosis mice. Materials and Methods: Mice were fed a high-fat diet (HFD), normal diet or an HFD supplemented with folic acid (20 μg/mL in drinking water) for 16 weeks. Throughout the 16 weeks study period, the rats were weighed once every week. GTT, ITT and lipid indexes were detected to evaluate the effects of folic acid on lipid metabolism in high-fat diet-fed mice. Morphological and structural changes of the femur and tibial bone were observed using micro-CT, HE staining and bone conversion parameters. The expression of MDA, SOD and inflammatory factors were detected to evaluate the effects of folic acid on oxidative stress and inflammatory response in high-fat diet-fed mice. Quantitative real-time PCR and Western blot (WB) were used to investigate the AMPK signaling pathway. Results: After the intervention of folic acid, the body fat rate of obese mice was reduced, and related metabolic disorders such as insulin resistance, hyperlipidemia, and systemic inflammation were alleviated. In correlation with those modifications, folic acid attenuated bone loss and improved bone microarchitecture accompanied the number of osteoclasts and adipocytes decreased. Furthermore, folic acid promoted the phosphorylation of AMPK, thereby promoting the expression of CPT1, Nrf2 and antioxidant enzymes. Conclusions: These findings suggest that folic acid may modulate lipid metabolism and oxidative stress responses through the activation of AMPK signaling pathway, thereby alleviating high-fat diet-induced osteoporosis. The results from our study provide experimental evidence to prevent high-fat diet-induced osteoporosis.